AGRIBUSINESS BEHAVIOR OF MANGO FARMERS IN THE DISTRICT OF PANYINGKIRAN MAJALENGKA REGENCYBASED ON MANGO OWNERSHIP - Rasmikayati, Elly; Saefudin, Bobby Rachmat; Nadapdap, Hendrik Johannes; Awaliyah, Fitri (Universitas Padjadjaran, 2020)
Mango varieties of Arumanis and GedongGincu is one of the horticultural commodities that are superior to Indonesian exports. The high local and international demand also makes the consumers preference of mango higher. Nevertheless, the development of mango agribusiness related to behavior of agribusiness farmers and the amount of mango trees is still not optimal. This study aims to determine the relationship between the agribusiness behavior of mango farmers and the number of mango trees. The method used in this study is a survey method with descriptive statistical and Chi-Square analysis tools. The results showed that the majority of mango farmers in Panyingkiran sub-district, Majalengka regency are farmers with narrow land (0.1-1 Ha) with the status of privately land. Farmers with privately status is command <50 mango trees on their land, while farmers who control > 200 mango trees are farmers with rental tree status. Farmers with little, medium, and large amounts of mango trees use private capital to cultivate mangoes and easily gain access to farm credit. The farmer makes the middleman as the final market destination and uses a cash payment system in buying and selling transactions. There are 6 variables of agribusiness behavior of mango farmers in Panyingkiran District, Majalengka Regency, which have a good and significant relationship with mastery of the number of mango trees, namely access to farm credit, application of off season technology, percent of good quality yields (grade A / B), determinants selling prices, payment systems and membership in farmer groups.